Enhanced priming of old, not new soil carbon at elevated atmospheric CO2. (September 2016) - Vestergård, Mette; Reinsch, Sabine; Bengtson, Per; Ambus, Per; Christensen, Søren
Abstract: Rising atmospheric CO2 concentrations accompanied by global warming and altered precipitation patterns calls for assessment of long-term effects of these global changes on carbon (C) dynamics in terrestrial ecosystems, as changes in net C exchange between soil and atmosphere will impact the atmospheric CO2 concentration profoundly. In many ecosystems, including the heath/grassland system studied here, increased plant production at elevated CO2 increase fresh C input from litter and root exudates to the soil and concurrently decrease soil N availability. Supply of labile C to the soil may accelerate the decomposition of soil organic C (SOC), a phenomenon termed 'the priming effect', and the priming effect is most pronounced at low soil N availability. Hence, we hypothesized that priming of SOC decomposition in response to labile C addition would increase in soil exposed to long-term elevated CO2 exposure. Further, we hypothesized that long-term warming would enhance SOC priming rates, whereas drought would decrease the priming response. We incubated soil from a long-term, full-factorial climate change field experiment, with the factors elevated atmospheric CO2 concentration, warming and prolonged summer drought with either labile C (sucrose) or water to assess the impact of labile C on SOC dynamics. We used sucrose with a 13 C/ 12 C signature that is distinct from that of the native SOC, which allowed us to assess the contribution of these two C sources to the CO2 evolved. Sucrose induced priming of SOC, and the priming response was higher in soil exposed to long-term elevated CO2 treatment. Drought tended to decrease the priming response, whereas long-term warming did not affect the level of priming significantly. We were also able to assess whether SOC-derived primed C in elevated CO2 soil was assimilated before or after the initiation of the CO2 treatment 8 years prior to sampling, because CO2 concentrations were raised by fumigating the experimental plots with pure CO2 that was 13 C-depleted compared to ambient CO2 . Surprisingly, we conclude that sucrose addition primed decomposition of relatively old SOC fractions, i.e. SOC assimilated more than 8 years before sampling. Highlights: Labile C primed decomposition of soil organic C in a heath/grassland ecosystem. 8 years of elevated CO2 exposure enhanced priming of soil organic C. Drought and warming impacts on soil organic C priming were less pronounced. Primed C derived from old soil C assimilated before elevated CO2 treatments started.